New information on the anatomy and histology of Gracilisuchus stipanicicorum (Archosauria: Pseudosuchia) from the Chañares Formation (early Carnian), Argentina - Lecuona, Agustina (2020)
Gracilisuchus stipanicicorum is a basal suchian from the Late Triassic Chañares Formation (Argentina), nested in the recently erected Gracilisuchidae, along with Turfanosuchus dabanensis and Yonghesuchus sangbiensis from China. The six known Gracilisuchus specimens preserve most of the skeleton, lacking most of the scapular girdle and forelimb. Our latest fieldworks have unearthed two specimens preserving previously unknown elements, including the humerus, radius, and ulna, as well as the femur, presacral vertebrae, and paramedian osteoderms. The femur and osteoderms were histologically sectioned, a study never undertaken in Gracilisuchidae. The anatomical analysis revealed characters in the new elements that improve the understanding of the anatomy of Gracilisuchus and its identification. Bone histology revealed that the specimen CRILAR PV 490 died before reaching somatic maturity and that growth was relatively slow compared to other pseudosuchians. This study deepens the knowledge of the anatomy of Gracilisuchus and constitutes a further step towards a broader understanding of Gracilisuchidae and basal suchian clades.